Respuesta :

gmany

[tex]\dfrac{2}{7k}(k-7)\qquad|\text{use distributive property}\\\\=\left(\dfrac{2}{7k}\right)(k)-\left(\dfrac{2}{7k}\right)(7)=\dfrac{2}{7}-\dfrac{2}{k}[/tex]

ANSWER

B.
[tex] \frac{2}{7k} (k - 7) = \frac{2}{7}- \frac{2}{k} [/tex]



EXPLANATION

The given expression is

[tex] \frac{2}{7k} (k - 7)[/tex]
where k≠0

We expand the bracket to get,


[tex] \frac{2}{7k} (k - 7) = \frac{2}{7k} \times k - \frac{2}{7k} \times 7[/tex]



We now cancel out the common factors to obtain,


[tex] \frac{2}{7k} (k - 7) = \frac{2}{7} \times 1- \frac{2}{k} \times 1[/tex]



We now simplify to obtain,

[tex] \frac{2}{7k} (k - 7) = \frac{2}{7}- \frac{2}{k} [/tex]


The correct answer is option B.

ACCESS MORE